Agendas for 21st century engineers - Brandt, Caroline,; Prescott, David (Cambridge Scholars Publishing, 2013)
This book is for engineers of different disciplines, such as chemical, electrical, petroleum, mechanical and civil engineering, and will appeal both to the experienced professional engineer and to undergraduate or postgraduate engineering students. This singular volume presents selected articles on themes that arise at the interface between engineering and the different societies in which it is practised. Themes of current interest include ethics, gender balance, education, workplace preparation, communication, competencies, and the future of engineering. Original and thought-provoking articles on these themes are presented by authors who have achieved international recognition for their work in engineering research, practice and education, and who work in different capacities in industry or higher education around the world. Recognizing the pluralism that is characteristic of such themes, each chapter presents two articles reflecting distinct perspectives and contexts. This volume therefore provides ideal opportunities for readers who wish to develop their critical thinking capacities by contrasting and evaluating the different viewpoints. It also provides readers with writing that complements the technical discourse predominant in engineering workplaces and institutes. This book, therefore, while promoting professional literacy and thinking skills development, concurrently serves to cultivate the well-rounded and forward-looking engineers required by the international community to meet the multifaceted challenges of 21st century engineering. --